Pengaruh Profil Pasien Kanker yang Mendapat Kemoterapi dengan Chemotherapy Induced Nausea and Vomiting (CINV) - Kardiyudiani, Ni Ketut; Afrida, Maryudella; Rahayu , Novi Widyastuti; Indriyani, Sita; Quiambao, Bernadette D (Ners Akademika, 2024)
Purpose: This study aimed to examine the effect of cancer patient profiles receiving chemotherapy on Chemotherapy-Induced Nausea and Vomiting (CINV). This study aimed to identify the factors related to the development of CINV in patients with cancer undergoing chemotherapy and to provide a better understanding of how patient characteristics influence their vulnerability to these side effects. Methods: This was a quantitative study with a correlation study design. The sample size consisted of 37 patients who had received chemotherapy. The Rhodes Index of Nausea, Vomiting, and Retching (RINVR) was used, with multivariate data analysis through multiple regression. Results: Among the 37 samples, the most common data findings were female sex (75.6%), age 41-65 years (78.4%), breast cancer type (43.2%), cancer stage 3-4 (29.7%), chemotherapy cycle 1-4 (54.1%), and mild CINV (70.27%). The relationship between the demographic profiles and CINV was significant, with a p-value of 0.000. The F-value was 37.561 and the R-squared value was 0.688. Meanwhile, the relationship between chemotherapy profiles, such as cancer type, cancer stage, and chemotherapy cycle, had an F-value of 42.081 and an R-squared value of 0.793.0.793. Limitations: This study may have a limited sample size, which could affect the reliability and generalizability of the findings. Larger sample sizes would provide more robust and representative data. Contributions: This study provides valuable insights into how various profiles of cancer patients (such as age, sex, type of cancer, and overall health) may influence the likelihood of experiencing chemotherapy-induced nausea and vomiting.